Pectoral spine size in Synodontis schall (Teleostei: Mochokidae) from Asa Lake, Ilorin, Nigeria - Araoye, P A (2000)
The pectoral spines of Synodontis schall (n = 813) were examined for 24 months. Mean length for the right (3.2 cm) and lefl (3.1 cm) pectoral spines were not significantly different lP> 0.05]. However, the male and female pectoral spine lengths were significantly different CP < 0.05). A fractured pectoral spine in one of the specimens was sborter than the other. The fracture which could be deleterious to balancing, feeding and reproductive activities was attributed to an injury rather than to genetíc or epigenetic defects.